The diagnosis of bladder cancer. - da Silva, C (1999)
Mandatory examination: physical exam including, digital rectal examination; renal and bladder ultrasound and/or IVP, cystoscopy with full description of the lesion and with a diagram, urinalysis, urinary cytology; TUR with biopsy of the tumor base, biopsy of all suspicious areas; randomised biopsies in presence of positive cytology, tumor > 3 cm or non papillary tumour; biopsy of the prostatic urethra in cis or when there is suspicion of cis. When the tumor is invasive, it is mandatory to perform chest X-ray, IVP, and or abdominal and pelvic CT scan, liver ultrasound and bone scan, if there are symptoms or a high alkaline phosphatase.